Correction: Calpain and Reactive Oxygen Species Targets Bax for Mitochondrial Permeabilisation and Caspase Activation in Zerumbone Induced Apoptosis. - Praveen K Sobhan; Mahendra Seervi; Lokesh Deb; Saneesh Varghese; Anjana Soman; Jeena Joseph; Krupa Ann Mathew; Godi Raghu; George Thomas; E Sreekumar; S Manjula; T R Santosh Kumar (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0059350.].